Reason in the rhyme: The translation of sound and rhythm in children's books - Ham, Linda (University of Ottawa (Canada), 2007)
Because child readers are still in the process of fully acquiring their language, children's books and their translations are closely linked to orality and the oral culture. Strong sound, rhyme and rhythm, which are habitual features of children's literature, also figure as important agents in the acquisition of language. Therefore, these linguistic principles might indicate a pedagogical skopos in the translation of children's literature, that of aiding in child language acquisition. Theory on sound translation and commentaries from translators of children's literature provide arguments for the importance of retaining sound and rhythm in translation. Analyses of three French-Canadian children's books translated into English provide practical observations of how sound and rhythm are translated in actual texts.
Keywords: Literature, Canadian (English).; Literature, Canadian (French).; Language, General.